2002
DOI: 10.2355/isijinternational.42.1103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mold Level Hunching by Unsteady Bulging during Thin Slab Casting.

Abstract: In order to analyze the phenomenon of mold level hunching (MLH) during thin slab casting process, the variation of the mold level and the bulging of strand were measured and analyzed using Fast Fourier Transform (FFT) spectrum analysis. Both of mold level hunching and bulging had the same frequency and the specific frequency corresponded to the main roll pitch of the thin slab caster. The unsteady bulging was found to be a main reason of mold level hunching. The unsteady bulging profile through the full range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Involving an expression for the local heat-transfer coefficient inside the mold (Yoon et al, 2002) a more realistic formula was derived that exhibited good results in the present study: …”
Section: The Heat Transfer Model Appliedmentioning
confidence: 81%
See 1 more Smart Citation
“…Involving an expression for the local heat-transfer coefficient inside the mold (Yoon et al, 2002) a more realistic formula was derived that exhibited good results in the present study: …”
Section: The Heat Transfer Model Appliedmentioning
confidence: 81%
“…Consequently, internal structure problems could be identified and verified in practice. The unsteady bulging was found to be (Yoon et al, 2002) the main reason of mold level hunching during thin slab casting. A finite difference scheme for the numerical solution of the heat transfer equation together with a continuous beam model and a primary creep equation were developed in order to match experimental data.…”
Section: Previous Work and Current Statusmentioning
confidence: 94%
“…As the generation mechanism of unsteady bulging, it is considered that the plastically deformed solidified shell does not remain in its original shape, and the shell is pushed back by the rolls, as Yoon et al 9) reported. In this simulation, as shown in Fig.…”
Section: Generation Mechanism Of Unsteady Bulgingmentioning
confidence: 99%
“…Yoon et al 9) have reported that unsteady bulging was suppressed by adoption of a non-cyclic roll pitch.…”
Section: Almentioning
confidence: 99%
“…However, bulge deformation measurement has been a very difficult problem to be solved due to the production feature of continuous casting. Only a few papers [1,2] presented experimental data of bulge deformation. In recent years, some measurement methods and patents have been proposed, but these methods applied in bulge deformation measurement have not been reported.…”
Section: Introductionmentioning
confidence: 99%